RAYAP MACROTERMES GILVUS (HAGEN) (ISOPTERA: TERMITIDAE) SEBAGAI HAMA PENTING PADA TANAMAN JARAK PAGAR (J. CURCAS) DI KEBUN INDUK JARAK PAGAR (KIJP) PAKUWON SUKABUMI JAWA BARAT - Muhammad Sayuthi (Universitas Syiah Kuala, 2012)
The main problem castor plantation (Jatropha curcas L.) is a pest Macrotermes gilvus result in lower production in terms of both quality and quantity. The research was conducted in August 2010. This research aims to study the pest M. gilvus to castor plantation in KIJP Pakuwon. The intensity of the attack M. gilvus in castor plantation in Block I (33%), Block II (27%) and Block III (15%), and if not immediately controlled can cause economic losses.